Serving All Who Served: An Analysis of the VA's Visual and Digital Rhetorics for Welcoming Sexual and Gender Minority Veterans Into VA Care. Issue 4 (15th December 2019) - Puntasecca, Christina; Hall, E. Ashley; Ware, Jennifer
Abstract : Nearly one million veterans identify as lesbian, gay, bisexual, and transgender (LGBT) and could be eligible for services provided by the United States Department of Veteran Affairs (VA). Historical criminalization of service members prior to and during the Don't Ask Don't Tell policy created social and cultural barriers to LGBT veterans seeking VA care. To date, no studies have assessed the implementation of the VA's efforts to create a welcoming environment for LGBT veterans. This study fills that gap by using rhetorical genre studies to analyze how official VA.gov websites position and address LGBT veterans. Our results indicate that rhetorical and discursive strategies deployed on the VAMC web sites betray information asymmetries reflecting varying levels of ambition and commitment to inclusion of LGBT veterans. With a focus on techne, we conclude with research‐based recommendations for VA practitioners, administrators, and policymakers to improve patient‐provider communication through public digital rhetorics.